Effects of Shareholder Information on Corporate Decisions and Capital Market Equilibrium - Kanodia, Chandra (Econometrica, 1980)
This paper examines the effect that imperfectly informed capital market agents have on the equilibrium paths of output, investment, and asset prices of value maximizing firms. Though information is imperfect, rational expectations is imposed as an equilibrium condition. It is found that both asset prices and corporate decisions are simultaneously affected in such a way that the efficiency-optimality relationship between them is pre- served. The effect of a fuller information structure is to move the economy from one efficient markets equilibrium to another. elaborated. Extant beliefs regarding accounting information are crystallized at two polar extremes. Policy-making bodies like the SEC and the FASB and most prac- titioners believe that investors are naive in processing information, and are principally concerned with the earnings per share figure as reported by accoun- tants. Investor decision rules are invariant to the rules for computing income, and therefore if the right or proper measure of income were not adopted, investors would be misled. In recent years stock price researchers have rapidly accumulated evidence against this naive investor hypothesis and in favor of the efficient markets hypothesis. For example, Kaplan and Roll (12) demonstrated that firms switching from the deferral method to the flow-through method for investment credit and firms switching from accelerated to straight-line deprecia- tion, in each case increasing their reported income, did not experience abnormal price increases. Sunder (23) found that firms switching from the FIFO to the LIFO method of inventory valuation, thereby decreasing their reported income, did not suffer in stock price performance. These findings raise a serious question. Do accounting statements have any informational impact on security prices at all? Several studies tested and rejected the null hypothesis that the periodic financial statements issued by corporations have no information content for capital market agents. Ball and Brown (1) tested for information content of the annual earnings report and found that foreknowledge of the earnings number could be used to generate excess returns. Brown and Kennelly (5) replicated the